Exploring the Probiotic, Antimicrobial, and Anticancer Potential of Aegle marmelos Kombucha: A Study on Natural Therapeutics (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study explores the probiotic, antibacterial, and cytotoxic potential of Aegle marmelos kombucha and synthesized bioactive compounds. The evaluation of Aegle marmelos kombucha revealed a substantial population of lactic acid bacteria (LAB), specifically Lactobacillus brevis and Leuconostoc mesenteroides, which contribute to the fermentation process and enhance the beverage's probiotic properties. Antibacterial activity of the kombucha extract was tested against four bacterial strains, with Staphylococcus aureus and Bacillus subtilis exhibiting the highest sensitivity. The kombucha extract showed concentration-dependent antibacterial effects, with inhibition zones ranging from 10 mm to 22 mm, suggesting its potential as a natural antimicrobial agent. Additionally, the cytotoxicity of synthesized compounds was assessed using MCF-7 (breast cancer) and HEK-293 (normal kidney) cell lines through MTT assays. The compounds demonstrated selective cytotoxic effects, with significant inhibition of MCF-7 cells at concentrations as low as 50 µg/ml, while showing lower toxicity toward HEK-293 cells. The IC50 for MCF-7 cells was approximately 60 µg/ml, compared to 400 µg/ml for HEK-293 cells, highlighting their cancer-targeting potential. In comparison, ursolic acid, a known anticancer agent, exhibited similar trends but with greater potency. These results indicate the potential of Aegle marmelos kombucha and synthesized compounds as probiotic, antimicrobial, and anticancer agents. The study’s findings underscore the relevance of natural bioactive products in health applications, with scope for further research into their mechanisms and potential synergy with conventional treatments.